Species differentiation of slipper orchids using color image analysis - Sanz, Ernesto; von Cramon Taubadel, Noreen; Roberts, David L. (Lankesteriana: International Journal on Orchidology, 2013)
A number of automated species recognition systems have been developed recently to aid nonprofessionals in the identification of taxa. These systems have primarily used geometric morphometric based techniques, however issues surround their wider applicability due to the need for homologous landmarks. Here we investigate the use of color to discriminate species using the two horticulturally important slipper orchid genera of Paphiopedilum and Phragmipedium as model systems. The ability to differentiate the various taxonomic groups varied, depending on the size of the group, diversity of colors within the group, and the background of the image. In this study the image analysis was conducted with images of single flowers of the species, however since flowers are ephemeral, flowering for a relatively short period of time, such analysis should be extended to vegetative parts, particularly as this is the form in which they are most often traded internationally.